Pain and Psychological Distress: Effect of Microvascular Decompression on Sleep Disorders and Obsessions in Trigeminal Neuralgia - Wang, Yanglingxi; Sun, Kai; Zhang, Wenling; Zhang, HaiTao; Wang, Chong (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study was aimed to investigate the effects of microvascular decompression (MVD) on sleep disorders and obsessions in trigeminal neuralgia.Methods Clinical data from 115 patients with trigeminal neuralgia treated with MVD from August 1, 2017 to May 31, 2018 at Jining First People's Hospital were analyzed retrospectively. The preoperative and postoperative risk factors for sleep disorders and obsessions, as well as the effects of MVD on sleep disorders and obsessions, were examined.Results In 115 patients, there were significant differences in preoperative sleep disorders associated with sex, monthly household income, pain in multiple branches, visual analog scale (VAS) score, and Self-Rating Depression Scale (SDS) score (p < 0.05). Preoperative obsessions were significantly different according to age, gender, pain in multiple branches, monthly household income, VAS score, and Self-Rating Anxiety Scale (SAS) score groups (p < 0.05). A 1-year recurrence was positively correlated with sleep disturbance (odds ratio = 3.829) and obsessions (odds ratio = 4.507). In addition, the results revealed a negative correlation between the manipulation of trigeminal neuralgia and postoperative sleep disorders (B ≥ 1.043). Moreover, there was a significant difference in sleep disorders and obsessions before and 1 year after MVD (p < 0.05).Conclusion For patients with trigeminal neuralgia, pain caused by sleep and obsession disorders should be examined early to identify an effective solution. Moreover, MVD, as a first treatment, is valuable for improving the physiological and psychological prognosis of patients.
Keywords: trigeminal neuralgia; microvascular decompression; sleep disorders; obsessions